Analisis Faktor-Faktor yang Mempengaruhi Keaktifan Individu pada Komunitas Online - Rafly Ardiansyah Ikhsantyo; Diah Priharsari; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Not all online communities succeed in inviting their members to be active in them. There is a theory called